Microbiota composition of the koala (Phascolarctos cinereus) ocular and urogenital sites, and their association with Chlamydia infection and disease - Vidgen, Miranda E. (Sci Rep, 2017)
Disease caused by Chlamydia pecorum is characterised by ocular and urogenital infections that can lead to blindness and infertility in koalas. However, koalas that are infected with C. pecorum do not always progress to disease. In other host systems, the influence of the microbiota has been implicated in either accelerating or preventing infections progressing to disease. This study investigates the contribution of koala urogenital and ocular microbiota to Chlamydia infection and disease in a free ranging koala population. Using univariate and multivariate analysis, it was found that reproductive status in females and sexual maturation in males, were defining features in the koala urogenital microbiota. Changes in the urogenital microbiota of koalas is correlated with infection by the common pathogen, C. pecorum. The correlation of microbiota composition and C. pecorum infection is suggestive of members of the microbiota being involved in the acceleration or prevention of infections progressing to disease. The analysis also suggests that multiple microbes are likely to be associated with this process of disease progression, rather than a single organism. While other Chlamydia-like organisms were also detected, they are unlikely to contribute to chlamydial disease as they are rare members of the urogenital and ocular microbiota communities.